AN INVESTIGATION INTO COMPREHENSION ERRORS IN ENGLISH-VIETNAMESE TRANSLATION AMONG ENGLISH MAJORED JUNIORS AT DONG A UNIVERSITY AND SUGGESTED SOLUTIONS - Le Ngoc Tran Chau, Le Ngoc Tran Chau; Nguyen Thanh Duc, Nguyen Thanh Duc (Tạp chí Khoa học Đại học Đông Á, 2025)
In the 21st century, English translation has surged in significance, emerging as an indispensable tool for students, individuals, various organizations, and commercial enterprises operating on a global scale. It can be said that effective translation requires a thorough understanding of diverse text genres. However, many students still encounter difficulties in comprehending various types of texts. This study attempts to investigate common mistakes that third-year English majors at Dong A University often encounter. To address this issue, questionnaires were used to collect data. Brief descriptions of the participants and data collection methods were also provided. The results showed that most students faced difficulties related to comprehension errors during the translation process from the source language (English) to the target language (Vietnamese). Based on the findings, the study proposed several solutions to improve students’ translation competence and suggested implications for lecturers in their teaching.